Osteocytes Enhance Osteogenesis by Autophagy-Mediated FGF23 Secretion Under Mechanical Tension - Xu, Huiyue; Xia, Meng; Sun, Lian; Wang, Hua; Zhang, Wei-Bing (Frontiers in Cell and Developmental Biology, 2022)
Mechanical stimuli control cell behaviors that are crucial for bone tissue repair. Osteocytes sense extracellular mechanical stimuli then convert them into biochemical signals to harmonize bone remodeling. However, the mechanisms underlying this process remain unclear. Autophagy, which is an evolutionarily preserved process, that occurs at a basal level when stimulated by multiple environmental stresses. We postulated that mechanical stimulation upregulates osteocyte autophagy via AMPK-associated signaling, driving osteocyte-mediated osteogenesis. Using a murine model of orthodontic tooth movement, we show that osteocyte autophagy is triggered by mechanical tension, increasing the quantity of LC3B-positive osteocytes by 4-fold in the tension side. Both in vitro mechanical tension as well as the chemical autophagy agonist enhanced osteocyte Fibroblast growth factor 23 (FGF23) secretion, which is an osteogenenic related cytokine, by 2-and 3-fold, respectively. Conditioned media collected from tensioned osteocytes enhanced osteoblast viability. These results indicate that mechanical tension drives autophagy-mediated FGF23 secretion by osteocytes, promoting osteogenesis. Our findings highlight a potential strategy for accelerating osteogenesis in orthodontic clinical settings.